Skip to main content
MathJax: \lim
Source Link
Martin Sleziak
  • 4.7k
  • 4
  • 35
  • 40

For a function $u\in W^{1,p}$, we always use a sequence of $C^1$ function to approach it and derive the consequences. However, can we just claim for a.e. x, y:

$$u(x)-u(y)= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

I tried to prove that it’s right in the following way:

Consider a $C^1$ sequence $u_n$ approaching u in $W^{1,p}$, the key here is to prove:

$$\int_0^1 D(u-u_n)(y+t(x-y))\cdot (x-y) dt$$

Tends to 0 as n tend to infinity, as we have, for a.e. x:

$$u_n(x) \to u(x)$$

Therefore, we have, for a.e. x, y:

$$ u(x)-u(y)=lim_{n\to\infty} u_n(x)-u_n(y)=lim_{n\to\infty} \int_0^1 Du_n(y+t(x-y))\cdot (x-y) dt= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$$$ u(x)-u(y)=\lim_{n\to\infty} u_n(x)-u_n(y)=\lim_{n\to\infty} \int_0^1 Du_n(y+t(x-y))\cdot (x-y) dt= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

For a function $u\in W^{1,p}$, we always use a sequence of $C^1$ function to approach it and derive the consequences. However, can we just claim for a.e. x, y:

$$u(x)-u(y)= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

I tried to prove that it’s right in the following way:

Consider a $C^1$ sequence $u_n$ approaching u in $W^{1,p}$, the key here is to prove:

$$\int_0^1 D(u-u_n)(y+t(x-y))\cdot (x-y) dt$$

Tends to 0 as n tend to infinity, as we have, for a.e. x:

$$u_n(x) \to u(x)$$

Therefore, we have, for a.e. x, y:

$$ u(x)-u(y)=lim_{n\to\infty} u_n(x)-u_n(y)=lim_{n\to\infty} \int_0^1 Du_n(y+t(x-y))\cdot (x-y) dt= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

For a function $u\in W^{1,p}$, we always use a sequence of $C^1$ function to approach it and derive the consequences. However, can we just claim for a.e. x, y:

$$u(x)-u(y)= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

I tried to prove that it’s right in the following way:

Consider a $C^1$ sequence $u_n$ approaching u in $W^{1,p}$, the key here is to prove:

$$\int_0^1 D(u-u_n)(y+t(x-y))\cdot (x-y) dt$$

Tends to 0 as n tend to infinity, as we have, for a.e. x:

$$u_n(x) \to u(x)$$

Therefore, we have, for a.e. x, y:

$$ u(x)-u(y)=\lim_{n\to\infty} u_n(x)-u_n(y)=\lim_{n\to\infty} \int_0^1 Du_n(y+t(x-y))\cdot (x-y) dt= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

deleted 17 characters in body
Source Link
Holden Lyu
  • 421
  • 2
  • 9

For a function $u\in W^{1,p}$, we always use a sequence of $C^1$ function to approach it and derive the consequences. However, can we just claim for a.e. x, y:

$$u(x)-u(y)= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

I don’t think it’s right but I just can not figure out a counter example. So I tried to prove that it’s right in the following way:

Consider a $C^1$ sequence $u_n$ approaching u in $W^{1,p}$, the key here is to prove:

$$\int_0^1 D(u-u_n)(y+t(x-y))\cdot (x-y) dt$$

Tends to 0 as n tend to infinity, which can be derived from the definitionas we have, for a.e. x:

Is there any fault in this proof? I still don’t think it’s right but I can’t tell it$$u_n(x) \to u(x)$$

Therefore, we have, for a. Maybe I need some help heree. x, y:

$$ u(x)-u(y)=lim_{n\to\infty} u_n(x)-u_n(y)=lim_{n\to\infty} \int_0^1 Du_n(y+t(x-y))\cdot (x-y) dt= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

For a function $u\in W^{1,p}$, we always use a sequence of $C^1$ function to approach it and derive the consequences. However, can we just claim for a.e. x, y:

$$u(x)-u(y)= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

I don’t think it’s right but I just can not figure out a counter example. So I tried to prove that it’s right in the following way:

Consider a $C^1$ sequence $u_n$ approaching u in $W^{1,p}$, the key here is to prove:

$$\int_0^1 D(u-u_n)(y+t(x-y))\cdot (x-y) dt$$

Tends to 0 as n tend to infinity, which can be derived from the definition.

Is there any fault in this proof? I still don’t think it’s right but I can’t tell it. Maybe I need some help here.

For a function $u\in W^{1,p}$, we always use a sequence of $C^1$ function to approach it and derive the consequences. However, can we just claim for a.e. x, y:

$$u(x)-u(y)= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

I tried to prove that it’s right in the following way:

Consider a $C^1$ sequence $u_n$ approaching u in $W^{1,p}$, the key here is to prove:

$$\int_0^1 D(u-u_n)(y+t(x-y))\cdot (x-y) dt$$

Tends to 0 as n tend to infinity, as we have, for a.e. x:

$$u_n(x) \to u(x)$$

Therefore, we have, for a.e. x, y:

$$ u(x)-u(y)=lim_{n\to\infty} u_n(x)-u_n(y)=lim_{n\to\infty} \int_0^1 Du_n(y+t(x-y))\cdot (x-y) dt= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

Source Link
Holden Lyu
  • 421
  • 2
  • 9

Does Newton-Leibnitz apply to Sobolev space

For a function $u\in W^{1,p}$, we always use a sequence of $C^1$ function to approach it and derive the consequences. However, can we just claim for a.e. x, y:

$$u(x)-u(y)= \int_0^1 Du(y+t(x-y))\cdot (x-y) dt$$

I don’t think it’s right but I just can not figure out a counter example. So I tried to prove that it’s right in the following way:

Consider a $C^1$ sequence $u_n$ approaching u in $W^{1,p}$, the key here is to prove:

$$\int_0^1 D(u-u_n)(y+t(x-y))\cdot (x-y) dt$$

Tends to 0 as n tend to infinity, which can be derived from the definition.

Is there any fault in this proof? I still don’t think it’s right but I can’t tell it. Maybe I need some help here.